ความสัมพันธ์ระหว่างคุณลักษณะของคณะกรรมการตรวจสอบกับความระมัดระวังทางบัญชีของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - อาทิตยา เดชสุขุม (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aimed to study relationship between audit committee characteristics and accounting conservatism of companies listed on the Stock Exchange of Thailand. The data were collected from Bloomberg database and Annual Registration Statement (Form 56-1) published on the website of the Stock Exchange of Thailand from 2014 to 2018, which were 1,119 data in total. From the study conducted by multiple regression analysis using overview data in 5 years, it was found that the accounting and financial knowledge of the audit committee was positively correlated with accounting conservatism at the statistical significance level of 0.01. The size of the audit committee and the frequency of the audit committee meeting were not correlated with accounting conservatism, while the audit committee experience had a negative direction with the accounting conservatism at the statistical significance level of 0.05.